Pengembangan E-Learning Materi Fluida Dinamis Untuk Mengembangkan Keterampilan Berpikir Kreatif Siswa Sekolah Menengah Atas - Hana Aliyah Azhary; Ketang Wiyono (Department of Physics Education, Universitas Mataram, 2020)
Succesfully conducted a study entitled development of e-learning on the subject of dynamic fluid to develop studentÃ¢â¬â¢s creative thinking skill in senior high school. This research is aimed at generating e-learning on the subject of dynamic fluid valid and practical. This study is a Research and Development (R&D) using Rowntree model which in the procedure consisted of three stages: planning stage, development stage and evaluation stage. The evaluation stage employed were formative evaluation Tessmer which consisted of four stages: self evaluation, expert review, one-to-one evaluation, and small group evaluation. The data collection technique using walkthrough and questionnaires. The validity is assessed by three experts that is in content aspect, learning design aspect, and e-learning aspect. Of the results expert review obtained an average assessment of 93,73% with a very valid criteria. While on stage one-to-one evaluation showed an average assessment of 89,67% with a very practical criteria. In the small group evaluation, the result is an average percentage of 92,91% with a very practical criteria. Based on the result that e-learning on the subject of dynamic fluid to developing studentÃ¢â¬â¢s creative thinking skill in senior high school which have been developed into the criteria of very valid and very practical.